2006
DOI: 10.2466/pr0.98.1.79-84
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Communication with Parents on Sexual Topics: A Study of Young People in Taiwan

Abstract: Communication between parents and adolescents about adolescents' sexual behavior has been studied. However, the types of issues on which adolescents are willing to communicate with their parents have been scarcely discussed. A survey was conducted among a random sample of 1,204 junior high school students in Taipei. The survey probed into adolescents' communication with their parents as related to sex, including physical development, sexuality, choice of partner, frequency of dating, whom to date, and intimacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Relying on friends and media as primary sources for sexual information is worrisome, as the information is not evaluated by professionals and can be misleading. Thirty percent of our participants identified parents as their primary source of sexual information, which is encouraging, as prior research has reported limited parent-child sexual communication in adolescents and young adults (Yang & Wu, 2006;Meechamnan et al, 2014;Tung et al, 2015). However, the content of parent-child communication is unclear.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Relying on friends and media as primary sources for sexual information is worrisome, as the information is not evaluated by professionals and can be misleading. Thirty percent of our participants identified parents as their primary source of sexual information, which is encouraging, as prior research has reported limited parent-child sexual communication in adolescents and young adults (Yang & Wu, 2006;Meechamnan et al, 2014;Tung et al, 2015). However, the content of parent-child communication is unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Thirty percent of our participants identified parents as the primary source of sexual information is encouraging, as prior research has reported limited parent-child sexual communication in adolescents and young adults (Meechamnan et al, 2014; Tung et al, 2014; Yang &Wu, 2006). However, the content of parent-child communication is unclear.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, individuals who report that their family members approve of premarital sex were more likely to experience UIP. Therefore, students' family members, especially their parents must be involved in educational programs to foster their values related to responsible sexual behavior and wise decision making [21][22][23][24]. An optimal family centered approach is expected to create an environment where parents communicate with their adolescent children about sexual issues more frequently and with greater ease [21][22][23][24].…”
Section: Implications Of the Studymentioning
confidence: 99%